How to assess gay, bisexual and other men who have sex with men for chemsex. (21st April 2016) - Pakianathan, M R; Lee, M J; Kelly, B; Hegazi, A
Abstract : Objectives: Sexualised substance use, 'chemsex', is being increasingly reported by gay, bisexual and other men who have sex with men (GBMSM) in sexual health clinics. We aim to describe the evidence base and practical ways in which clinicians can assess and advise patients disclosing chemsex. Methods: We review published literature on chemsex, discuss vulnerability to substance use, highlight the importance of clinical communication and discuss a management approach. Results: GBMSM are vulnerable to substance use problems, which interplay with mental, physical and sexual health. Knowledge on sexualised drug use and related communication skills are essential to facilitating disclosure. Identifying sexual health and other consequences of harmful drug use may motivate patients to seek change. Conclusions: Sexual health clinicians are well placed to make more holistic assessments of GBMSM accessing their services to promote broader sexual health and well-being beyond the management of HIV and sexually transmitted infections (STIs) alone.